Inter-comparison of global precipitation data products at the river basin scale - Xiaolong Hu; Zheng Zhou; Haibin Xiong; Quan Gao; Xiayu Cao; Xuhai Yang (Hydrology Research, 2024)
While many studies have compared global precipitation datasets at national, continental, and global scales, few have evaluated these data at river basin scales. This study explored differences in precipitation estimates and trends of 12 widely applied precipitation datasets, including gauge-, satellite-, and reanalysis-based products, for the world's 6,292 river basins. Results showed that disparities between 12 precipitation datasets were considerable. A total of 3,125 river basins, with a land area of 5,989.1×104 km2, had differences in estimated annual average precipitation exceeding 500 mm yr−1, and these basins were mainly distributed in Greenland, Africa, Oceania, and West Asia. Disparities between the precipitation datasets were particularly large during the dry season when the percentage difference between the highest and lowest precipitation estimates exceeded 500% in 1,390 river basins (4,839.7×104 km2) expected due to numerical reasons. Differences in rainfall trends also varied markedly between data sources. The data products do not agree on precipitation trends for all river basins. These findings illustrate the importance of accurate precipitation data to ensure effective policy and planning in term of hydropower generation, domestic water supply, flood protection, and drought relief at river basin scales and highlight the uncertainty that exists in current global precipitation data. HIGHLIGHTS A comprehensive evaluation of global precipitation datasets was compared at the river basin scale.; Seasonal and annual differences in these precipitation datasets were compared.; Gives a sufficient explanation of which product is suitable for which river basin.;